Social/dialogical roles of social robots in supporting children’s learning of language and literacy—A review and analysis of innovative roles - Rohlfing, Katharina J.; Altvater-Mackensen, Nicole; Caruana, Nathan; van den Berghe, Rianne; Bruno, Barbara; Tolksdorf, Nils F.; Hanulíková, Adriana (Frontiers in Robotics and AI, 2022)
Social robots are designed for many purposes, one of which is education. There have been many attempts to systematize the potential that social robots have for this field. They have in common that learning can be supported in a variety of ways reflecting the fact that a learner can be engaged in different activities that foster learning. To design these activities, so far, three classical roles of a robot have been proposed: as a teacher or tutor, a learning peer, or a novice. Current research proposes that the decision on one role over the other depends on the content or the pedagogical form preferred. However, the design of activities does not only change the content of learning, but also the nature of a human–robot social relationship. This is particularly important for the acquisition of language, which has been recognized as a social endeavor. In the following review, we aim to specify the differences in human–robot social relationships when children learn language by interacting with a social robot. Proposing categories for the comparison of different relationships, we will review classical and innovative roles that a robot can play in language learning scenarios. Hereby, we follow the theoretical account by Mead (1946) proposing that social roles are performed in interactive acts. For learning, these acts are crucial as they cannot only shape the social environment of learning but also engage the learner to a different degree. We specify the degree of engagement referring to Chi’s (2009) progression accounting for learning activities that range from active, constructive, toward interactive with the latter fostering deeper learning. Together, this approach enables us to compare and evaluate different human–robot social relationships that arise when applying a robot in a particular social role.